2004
DOI: 10.1677/joe.0.1820173
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of G-protein-coupled receptor kinases 3 and 4 in hyperfunctioning thyroid nodules

Abstract: G-protein-coupled receptor kinases (GRKs) are implicated in the pathophysiology of human diseases such as arterial hypertension, heart failure and rheumatoid arthritis. While G-protein-coupled receptor kinases 2 and 5 have been shown to be involved in the desensitization of the rat thyrotropin receptor (TSHR), their role in the pathophysiology of hyperfunctioning thyroid nodules (HTNs) is unknown. Therefore, we analyzed the expression pattern of the known GRKs in human thyroid tissue and investigated their fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…demonstrated in differentiated thyroid carcinoma cells (Metaye et al, 2002). In previous investigations we found an expression of GRKs 2 ± 6 in human thyroid tissue (Voigt et al, 2004). We could demonstrate that GRK 2, 3, 5 and 6 are able to desensitize the TSH receptor in vitro by coexpression of the different GRKs with the TSH receptor in HEK 293 cells and we found an increased expression of GRK 3 and 4 in hyperfunctioning thyroid nodules (HTNs) compared to their surrounding thyroid tissue (Voigt et al, 2004).…”
Section: Introductionsupporting
confidence: 54%
“…demonstrated in differentiated thyroid carcinoma cells (Metaye et al, 2002). In previous investigations we found an expression of GRKs 2 ± 6 in human thyroid tissue (Voigt et al, 2004). We could demonstrate that GRK 2, 3, 5 and 6 are able to desensitize the TSH receptor in vitro by coexpression of the different GRKs with the TSH receptor in HEK 293 cells and we found an increased expression of GRK 3 and 4 in hyperfunctioning thyroid nodules (HTNs) compared to their surrounding thyroid tissue (Voigt et al, 2004).…”
Section: Introductionsupporting
confidence: 54%
“…Moreover, it is important to note that a particular GRK does not have to be the most prominently expressed GRK in a tissue to be crucial for a specific GPCR signaling regulation as its cellular localization and activity are key measures determining GPCR-GRK interactions. More recently, GRK3 and GRK4 have been described to be present in the thyroid nodules and to be upregulated in hyperfunctioning thyroids, which may also indirectly impact cardiac function (262).…”
Section: B Grk Tissue Localizationmentioning
confidence: 99%
“…A key role for GRK2, GRK5, and GRK6 was first demonstrated in the TSH receptor homologous desensitization using a rat thyroid cell line (FRTL-5; Iacovelli et al 1996, Nagayama et al 1996a). Subsequently, GRK3 was also shown to desensitize the TSH receptor in HEK 293 cells (Voigt et al 2004). A predominant role for GRK5 (Metaye et al 2002) and GRK3 (Voigt et al 2004) has been suggested in differentiated thyroid carcinomas (DTC) and hyperfunctioning thyroid nodules respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A predominant role for GRK5 (Metaye et al 2002) and GRK3 (Voigt et al 2004) has been suggested in differentiated thyroid carcinomas (DTC) and hyperfunctioning thyroid nodules respectively. Furthermore, these findings were reinforced by the detection of GRK proteins in human thyroid tissues (Voigt et al 2004), with a major expression of GRK2 and GRK5 (Nagayama et al 1996a, Metaye et al 2002.…”
Section: Introductionmentioning
confidence: 99%